Hybrid Inflation Targeting Regimes - Garcia, Carlos (IMF Working Papers; Working Paper, 2009)
This paper uses a DSGE model to examine whether including the exchange rate explicitly in the central bank's policy reaction function can improve macroeconomic performance. It is found that including an element of exchange rate smoothing in the policy reaction function is helpful both for financially robust advanced economies and for financially vulnerable emerging economies in handling risk premium shocks. As long as the weight placed on exchange rate smoothing is relatively small, the effects on inflation and output volatility in the event of demand and cost-push shocks are minimal. Financially vulnerable emerging economies are especially likely to benefit from some exhange rate smoothing because of the perverse impact of exchange rate movements on activity.